ETNOGRAFIEN I KAMERAET - Møhl, Perle (Tidsskriftet Antropologi, 1995)
Perle Møhi: Ethnography in the Camera Taking the point of departure in filmed ethnography, the author discusses the rela- 219 tions between the ethnographer and the people who are studied seen in relation to the production of knowledge. Through a description of how the camera can be used in the field both clearly to mark which part of the field is under investigation - the one pointed out by the lense - and when it is under investigation - when the camera is on and off - it is argued that the use of the camera in the field, ideally, works to make the ethnographic investigation both more visible and in a sense more democratic. This, however, also bears some potential for written ethnography, which is another consideration in the article.